2016
DOI: 10.3109/07435800.2016.1141945
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific associations of genetic variants with metabolic syndrome components in the Tunisian population

Abstract: Our results reveal new candidate genes for MetS in the Tunisian population and suggest that the genetic basis of this syndrome is gender dependent. Further studies are necessary to understand why these associations differ between males and females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 38 publications
4
14
0
1
Order By: Relevance
“…No study was interested in measuring the association between rs4420638 polymorphism and obesity previously. No association was reported for the rs4420638 with MetS, T2D, and HBP; similar results were observed in a Tunisian population [27].…”
Section: Discussionsupporting
confidence: 75%
“…No study was interested in measuring the association between rs4420638 polymorphism and obesity previously. No association was reported for the rs4420638 with MetS, T2D, and HBP; similar results were observed in a Tunisian population [27].…”
Section: Discussionsupporting
confidence: 75%
“…The G allele of rs4420638 seems to confer a protective effect against obesity (OR 0.48,, p = 0.004), no study was interested in measuring association between rs4420638 polymorphism and obesity previously. No association was reported for the rs4420638 with MetS, T2D and HBP similar results were observed in Tunisian population (Elouej et al, 2016).…”
Section: Discussionsupporting
confidence: 72%
“…The result of GWAS also confirmed that changes around the KLF14 gene locus are closely related to HDL‐C levels, metabolic syndrome, and atherosclerosis . These studies have implicated a group of highly correlated SNPs including rs4731702 and rs972283 ~14 kb upstream of KLF14 .…”
Section: Klf14 and Cholesterol Metabolismmentioning
confidence: 59%
“…The result of GWAS also confirmed that changes around the KLF14 gene locus are closely related to HDL-C levels, metabolic syndrome, and atherosclerosis. 27,[31][32][33] These studies have implicated a group of highly correlated SNPs including rs4731702 and rs972283~14 kb upstream of KLF14. 27,31 Recently, researchers utilized chromatin state maps to annotate an interval, and identified a~1.6 kb enhancer~5 kb upstream of KLF14, which encompassed five T2D-associated variants and showed marked tissuespecificity.…”
Section: Klf14 and Cholesterol Metabolismmentioning
confidence: 99%